Polarization-independent beam deflection and focusing with dielectric non-resonant metasurfaces. (3rd August 2017) - Su, Xiaofang; Li, Guanhai; Yang, Hui; Zhao, Zengyue; Yu, Feilong; Chen, Xiaoshuang
Abstract: Metasurfaces, constructed from function-driven artificial meta-cells, possess great flexibility in tuning effective electric permittivity and magnetic permeability, leading to excellent performance on the manipulation of electromagnetic waves. Here, polarization-independent dielectric metasurfaces are presented as beam deflectors and meta-lenses working on telecommunication wavelength based on non-resonant metamolecules. A conversion efficiency as high as 70.5% is achieved when beam deflection angle θ = 18.45°. With precisely designed parameters, a planar lens with the focal length of 30.85 µ m shows that focusing efficiency as high as 47.3% is realized. The meta-lens yields a NA = 0.63 and a full-width at half-maximum (FWHM) = 1.64 µ m at 1.55 µ m. With broadband and wide-angle focusing properties, the polarization-insensitive metasurfaces promise great applications in high sensitivity single photon detector and other opto-electronic integrated devices.